2021
DOI: 10.1590/1518-8345.4269.3439
|View full text |Cite
|
Sign up to set email alerts
|

Duration of night sleep and cognitive performance of community older adults

Abstract: Objective: to analyze the relationship between the duration of self-reported night sleep and the cognitive performance of older adults. Method: the sample consisted of 156 older adults registered in Family Health Units (FHUs) in a city of São Paulo, divided into quartiles according to the duration of night sleep. Data collection was performed using a characterization questionnaire, Addenbrooke’s Cognitive Exam – Revised (ACE-R) and Pittsburgh Sleep Quality Index (PSQI). Descriptive, comparative and correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
3
0
6
Order By: Relevance
“…Os transtornos do sono são considerados frequentes na população idosa 3,25 . Na amostra estudada, 71,6% apresentaram distúrbios do sono leve e, em sua maioria ,não faziam uso de nenhum medicamento para dormir (72,4%), corroborando o descrito na literatura nacional e internacional 24,26 .…”
Section: Resultsunclassified
“…Os transtornos do sono são considerados frequentes na população idosa 3,25 . Na amostra estudada, 71,6% apresentaram distúrbios do sono leve e, em sua maioria ,não faziam uso de nenhum medicamento para dormir (72,4%), corroborando o descrito na literatura nacional e internacional 24,26 .…”
Section: Resultsunclassified
“…Over the years, and with the physiological changes resulting from age, SQ has been reduced 37 . Age influences the sleep parameters, and the physiological needs change throughout life 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Sleep duration per night was categorized into four groups: ≤5 hours, 6 hours, 7 hours, and ≥ 8 hours. Previous studies have suggested that 6 hours of sleep is bene cial, and thus 6 hours of sleep per night was used as the reference group [17,18,21].…”
Section: Sleep Durationmentioning
confidence: 99%
“…Meanwhile, a meta-analysis found that the relationship between sleep duration and the risk of cognitive dysfunction showed a Ushaped dose-response relationship, and individuals with sleep duration of 7-8 hours per night were at the lowest risk of cognitive impairment, sleep duration shorter or longer than this was associated with a higher risk of cognitive impairment [16]. At present, there are inconsistencies in the optimal sleep duration for the elderly, and previous studies have suggested that 6-8 hours of sleep is more appropriate for the stability of cognitive function [17,18]. While most of the population-based studies regarding the relation of sleep parameters with cognitive function have been conducted among urban populations.…”
Section: Introductionmentioning
confidence: 99%